Comparative analysis of hysteroscopy versus suction evacuation in the management of retained product of conception - K. M., Harish; N., Shwetha; Debnath, Dipankar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: RPOC can occur due to spontaneous or induced abortion followed by incomplete or partial expulsion of product of conception. Suction evacuation is currently the standard surgical treatment, but operative hysteroscopy has the advantage over Suction evacuation allowing the direct visualization of the retained conception product, facilitating its elective removal while limiting surgical complications. Methods: Comparative retrospective study of 80 patients who presented with RPOC during the period of 6 months. Hysteroscopy was done in 40 patients and Suction evacuation in remaining 40 patients. Data regarding anaesthesia required, mean time taken for procedure and post procedure hospital stay, complication due to the procedure and post-operative outcome were collected to compared, Results: In hysteroscopy group none of patients required anaesthesia and even though mean time taken for the procedure is 2 minutes more in hysteroscopy group without statistical significant difference (P 0.672), the post procedure hospital stay is less compared to suction evacuation group. Complication due to procedure was seen in 5 (12.5%) patients in hysteroscopy group which is less compared to 13 (32.5%) patients in suction evacuation group. Mean number of days of pain requiring analgesia and Sick leave applied was also less in hysteroscopy group (1 day and 2 days respectively) group compared to suction evacuation group (9 days and 7 days respectively) Conclusions: Lesser rates of intra and post-operative complications with hysteroscopy makes the procedure ‘safe’ to the patients and ‘effective’ as it ensures complete evacuation of the uterine cavity under direct vision and reduce the need for repeat procedure.